ANALISIS PENGARUH FOOD QUALITY, FOOD SAFETY, DAN TIME SAVING ORIENTATION MELALUI KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN ANNISA CATERING PADA MASA PANDEMI COVID-19 - Muhammad Adhitya Ramadhani; Farida Indriani (Diponegoro Journal of Management, 2022)
At the beginning of 2020 the world was shocked by the outbreak of a virus such as influenza and the disease was called Coronavirus disease 2019 (COVID-19). With this pandemic, consumer behavior has changed to full their needs. One of them is behavior in terms of purchasing food. For various reasons such as quality of food, food safety and orientation to save time, many consumers choose daily catering services to meet their daily food needs. Annisa Catering is one of the many catering businesses that are trying to adapt to this change in behavior. This study aims to determine how these three factors influence to build consumer loyalty Annisa Catering through customer satisfaction as an intervening variable. This research was conducted using a survey method to 115 respondents who had purchased Annisa Catering home catering more than once by filling out a questionnaire containing statements related to the variables used in this study. The data obtained were analyzed quantitatively and structurally using the Structural Equation Modeling (SEM) method using the Analysis Moment of Structural (AMOS) 24 program. The results of this research indicate that of the 7 proposed hypotheses, all hypotheses were successfully accepted positively significantly. Hypothesis 1 food quality on consumer satisfaction, Hypothesis 2 food safety on consumer satisfaction, Hypothesis 3 Time Saving Orientation on consumer satisfaction, Hypothesis 4 food quality on consumer loyalty, Hypothesis 5 food safety on consumer loyalty, Hypothesis 6 time saving orientation on consumer loyalty, and Hypothesis 7 consumer satisfaction on consumer loyalty.